Beat the Crisis: 33 Quick Solutions for Your Company - Simon, Hermann; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
"Stocks plunge on worries over financial sector" "Jobless rate at 14-year high" "Economy shrinks with consumers leading the way" "As home sales sag, foreclosures soar" "Retail chains caught in a wave of bankruptcies" Newspaper columns blare the news daily. There is no doubt that we are struggling through a worldwide economic and financial crisis of a magnitude not witnessed since the Great Depression. In this environment, fraught with danger, no company can afford to take a wait-and-see attitude. One hesitation or misstep can result in the rapid demise of a once stalwart enterprise. Even small miscalculations can topple mighty empires; consider the U.S. auto industry, for example. The severity of the crisis demands that your company understand its causes, diagnose carefully, implement decisively and monitor constantly. However, the crisis also creates chances for companies that learn to assess risk, recognize opportunity and take action quickly. This book is an antidote to the chorus of doom-and-gloom, a manual for business leaders and employees who are ready to fight. In Beat the Crisis, international strategy guru, Hermann Simon, offers 33 practical actions that any company can take immediately. Organized into broad categories$1 (B"Changing Customer Needs," "Sales and the Sales Force," "Managing Offers and Prices" and "Services," Simon shows companies how to focus on the areas where emphatic action can have quick and maximum impact on corporate performance. Drawing from dozens of successful cases around the world, Simon helps readers learn to read the market signals, develop quick solutions, and stay a step ahead of their competitors, while avoiding the pitfalls looming in the crisis. A concluding chapter looks beyond the crisis and considers the longer-term socio-political and business consequences, in which Simon foresees a new era of restraint. As he argues: "The 33 quick solutions won$1 (Bt rid the world of the crisis, but they can certainly contain the damage. And this can make all the difference between a company$1 (Bs death and survival." Can your company afford to ignore this advice? Hermann Simon is Chairman of Simon-Kucher & Partners, Strategy & Marketing Consultants, with offices in Europe, Asia, and the United States. He is an expert in strategy, marketing and pricing, advising clients and speaking to business organizations worldwide. Prior to taking on consulting full-time, he was a professor of business administration and marketing at the Universities of Mainz and Bielefeld, and has served as a visiting professor at many universities, including Harvard Business School, London Business School, INSEAD, Keio University, Stanford, and MIT. Named one of Europe$1 (Bs most influential management thinkers, he has served on the boards of numerous journals, including the International Journal of Research in Marketing, Management Science, and European Management Journal, and has published over 30 books, including the worldwide bestsellers Hidden Champions (1996), Power Pricing (1997), Manage for Profit, Not for Market Share (2006), and Hidden Champions of the 21st Century (2009).s
Diagnosing the Crisis -- What Works and What Doesn$1 (Bt Work Against the Crisis -- Intelligent Cost Cutting -- Quick Solutions for Changing Customer Needs -- Quick Solutions for Sales and the Salesforce -- Quick Solutions for Managing Offers and Prices -- Quick Solutions for Services -- Implementing the Quick Solutions -- Beyond the Crisis.s
Keywords: Economics; Industrial management; Marketing; Business planning; Economics/Management Science; Management/Business for Professionals; Business/Management Science, general; Organization/Planning.; Marketing